The Teacher Constraints in Implementation of Independent Curriculum At SD Negeri Unggul Lampeuneurut Aceh Besar Tahun 2022 - Aisyah Dwita Puspa Sari; Ahadin Ahadin; Fauzi Fauzi (Elementary Education Research, 2023)
AbstractThis research tries to reveal the obstacles faced by teachers in implementing the independent curriculum at SD Negeri Unggul Lampeneueurut Aceh Besar. The approach used in this research is qualitative and descriptive research type. Data collection is done through observation and interviews. The subjects of this study were 8 teachers who had implemented the independent curriculum. Then, the observation and interview data were arranged descriptively. The results of this study indicate that the average score of the observation data from the teacher's ability to implement independent curriculum learning is 2.34, which is included in the fairly good category. And based on the results of interviews, the teacher encountered obstacles in implementing the independent curriculum, namely: a) In the socialization or training on the independent curriculum, teachers are not supported by independent curriculum training. This resulted in a lack of teacher involvement in the training process that was held so that only 2 out of 8 teachers studied independently to gain experience and certificates, b) teachers were limited in obtaining references for implementing independent learning, c) sometimes teachers had difficulty accessing digital. media or the internet and d) lack of experience in implementing independent learning. Based on the results of data analysis, it can be concluded that: 1) The teacher's ability in carrying out learning with an independent curriculum is in a fairly good category. 2) Teachers experience several obstacles in implementing the independent curriculum at SD Negeri Unggul Lampeneueurut Aceh Besar.